Legal protection against children who are passed on in the transportation of two - wheeled vehicles on the highway (Research, Society and Development, 2020)
The research objective was to analyze and find the urgency and concept of legal protection for children in two-wheeled motorized vehicle transportation on the highway. This study uses a normative research method with a statutory approach, a conceptual approach, a comparative approach, a philosophical approach. There are clear rules regarding legal protection for children who take a ride in two-wheeled motorized vehicle transportation on the highway. Children often become victims of the misunderstanding of the parents/community who ride a child under 12 years old with a two-wheeled motorized vehicle on the road, parents/community don’t realize the risks posed by mistreatment by piggybacking children under 12 (twelve) years old with  two-wheeled motorized vehicles on the highway. With the existence of clear rules governing legal protection for children as passengers in two-wheeled motorized vehicle transportation, it’s hoped that parents/the community will realize and understand the safety of the child's soul.